2019
DOI: 10.1200/jco.18.01972
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Therapy for Combined Loss of Heterozygosity 1p and 16q in Favorable Histology Wilms Tumor: A Children’s Oncology Group AREN0532 and AREN0533 Study Report

Abstract: PURPOSE In National Wilms Tumor Study 5 (NWTS-5), tumor-specific combined loss of heterozygosity of chromosomes 1p and 16q (LOH1p/16q) was associated with adverse outcomes in patients with favorable histology Wilms tumor. The AREN0533/AREN0532 studies assessed whether augmenting therapy improved event-free survival (EFS) for these patients. Patients with stage I/II disease received regimen DD4A (vincristine, dactinomycin and doxorubicin) but no radiation therapy. Patients with stage III/IV disease received reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 20 publications
0
63
0
Order By: Relevance
“…The 2-year RFS reported for stage III FHWT patients registered in the NWTS-4 (91.1-95.3%) was comparable to stage I and II patients [38]. When adjusted for LOH 1p/16q (4-year RFS) and 1q gain (8-year RFS) in the subsequent NWTS-5 and AREN0532 and AREN0533 studies, relapse rates remained similar in all FHWT non-metastatic stages (Table 2) [29,42]. Similarly, in two UK studies with overlapping cohorts (UKW1-3 [46], and UKW2-3 and SIOP 2001 [47]), stage III was no longer of prognostic significance for recurrence when adjusted for copy number variations, including LOH 1p and/or 16q in both studies and 1q gain only in the latter (Table 3).…”
Section: Stage IIImentioning
confidence: 81%
See 2 more Smart Citations
“…The 2-year RFS reported for stage III FHWT patients registered in the NWTS-4 (91.1-95.3%) was comparable to stage I and II patients [38]. When adjusted for LOH 1p/16q (4-year RFS) and 1q gain (8-year RFS) in the subsequent NWTS-5 and AREN0532 and AREN0533 studies, relapse rates remained similar in all FHWT non-metastatic stages (Table 2) [29,42]. Similarly, in two UK studies with overlapping cohorts (UKW1-3 [46], and UKW2-3 and SIOP 2001 [47]), stage III was no longer of prognostic significance for recurrence when adjusted for copy number variations, including LOH 1p and/or 16q in both studies and 1q gain only in the latter (Table 3).…”
Section: Stage IIImentioning
confidence: 81%
“…Effective use of LOH 1p/16q in clinical practice is therefore limited to small patient subsets. AREN0532 or AREN0533 have used LOH of 16q/1p as treatment stratification factor, and these studies, which included therapy intensification for patients with LOH 16q/1p, showed significantly better 4-year EFS rates compared to the preceding NWTS-5 study (Table 2) [42]. The prognostic significance of LOH of 1p and/or 16q will be further validated for SIOP patients in UMBRELLA [2].…”
Section: Loh Of 1p and 16qmentioning
confidence: 97%
See 1 more Smart Citation
“…1 cm (Figure A1A in our article). 2 The event-free survival and overall survival estimates were nearly identical, indicating that the excellent results were not restricted to patients with small lung nodules and that augmented therapy had a beneficial effect.…”
mentioning
confidence: 81%
“…This tumor is an embryonal childhood tumor of metanephric origin, as it is histologically similar to the early stages of nephrogenesis, and many of the genetic changes that support the disease occur in genes associated with fetal kidney genes [ 2 ]. With the development of modern multimodality therapy, favorable histology WT survival has been achieved in more than 90% [ 3 5 ]. Of course, the described above does not include patients with advanced disease, bilateral WT patients and patients with recurrence.…”
Section: Introductionmentioning
confidence: 99%